2015
DOI: 10.4103/0973-1296.157665
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of some edible mushrooms extracts over liver hepatocellular carcinoma cells in conjunction with their antioxidant and antibacterial properties

Abstract: Background:Mushrooms have been valued for their nutritive content and as traditional medicines; several important medicinal properties of mushrooms have been recognized worldwide.Objective:The purpose of this study was to elucidate the cell growth inhibitory potential of four edible mushrooms; Coprinus comatus (O.F. Mull.) Pers. (Agaricaceae), Tricholoma fracticum (Britzelm.) Kreisel (Tricholomataceae), Rhizopogon luteolus Fr. and Nordholm (Rhizopogonaceae), Lentinus tigrinus (Bull.) Fr. (Polyporaceae) on hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 60 publications
2
13
2
Order By: Relevance
“…The antiradical scavenging activity of the D. tripetala aqueous seed extracts mentioned in this study is owing to the presence of phenols that usually possesess high metal-chelating activity. This result correlates with the reports of Jazek et al [30], Sadi et al, [31] and Ojo et al [32,33]. Tables 1 and 2].…”
Section: Discussionsupporting
confidence: 92%
“…The antiradical scavenging activity of the D. tripetala aqueous seed extracts mentioned in this study is owing to the presence of phenols that usually possesess high metal-chelating activity. This result correlates with the reports of Jazek et al [30], Sadi et al, [31] and Ojo et al [32,33]. Tables 1 and 2].…”
Section: Discussionsupporting
confidence: 92%
“…Hericium erinaceus has been demonstrated to play a role in chemotherapy resistance against HCC by facilitating intracellular doxorubicin accumulation through the inhibition of the NF-κB activity [11]. Extracts of edible mushroom have indicated considerable cytotoxic, antibacterial, and antioxidant properties in HCC HepG2 and may be utilized as a potent anti-infection drug against HCC [31]. Another study showed that the Akt/GSK-3β pathway facilitates the lowering of the CD44 and TGF-b1 migration in HCC cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 values of methanol and acetone extracts of T. focale, however, were 0.21 ± 0.01, and 0.40 ±0.01 mg/mL. Ferreira et al (2007) privously tested DPPH scavenging activity of methanol extract of another wild edible mushroom T. portentosum and found IC 50 as 40.2 mg/mL and Sadi et al (2015) found IC 50 as 3.25 mg/mL for T. fracticum which was not even close to T.imbricatum extracts. Tel et al (2011) worked on wild mushroom species namely T. fracticum, T. terreum and T. imbricatum with different extracts our result were comparable according to ABTS test.…”
Section: Antioxidant Activity Resultsmentioning
confidence: 99%
“…The various phytochemicals were isolated form the T. matsutake exhibiting anti-inflammatory, antioxidant and anticancer activities (Ding and Hou, 2012;Taofiq et al, 2016;You et al, 2013). Besides this species other Tricholoma species have been also attracted (Chen et al, 2017;Hassan et al, 2015;Sadi et al, 2015). Having the similar aim, we have performed complimentary antioxidant activity tests in addition to fatty acid analysis of T. imbricatum and T. focale to increase the knowledge.…”
Section: Introductionmentioning
confidence: 99%